2015
DOI: 10.9715/kila.2015.43.6.098
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Neighborhood Environmental Perception on Park Use for Health Improvement - The Case of Suseong-gu in Daegu City -

Abstract: The purpose of this study is to analyze the effect of neighborhood environmental perception on park use for health. The study area is focused on neighborhood parks in Suseong-gu, Daegu city. The analysis results are based on questionnaires of 303 respondents. According to the results, park use for health improvement was significantly associated with the perceptions of accessibility to a marketplace, availability of public transit, accessibility to the park, enough sidewalks, number of crosswalks, and athletic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Most studies (81%) used physical health-related variables to examine the relationship between the BE and health, including health-related behaviors, illness or death, and perceived health status. The health-related behaviors included moderate or high intensity physical activity, walking, sedentary behavior, and dietary behavior, with walking being the most common [29,32,38,40,41,45,46]. Obesity, allergic disease, and mortality were associated with the BE, and several studies reported a correlation between obesity and the BE [26,27,28,35,40,44,48].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies (81%) used physical health-related variables to examine the relationship between the BE and health, including health-related behaviors, illness or death, and perceived health status. The health-related behaviors included moderate or high intensity physical activity, walking, sedentary behavior, and dietary behavior, with walking being the most common [29,32,38,40,41,45,46]. Obesity, allergic disease, and mortality were associated with the BE, and several studies reported a correlation between obesity and the BE [26,27,28,35,40,44,48].…”
Section: Resultsmentioning
confidence: 99%
“…The density of intersections was highly related to the frequency of walking because of the smaller number and lower speed of automobiles and increased street connectivity [38]. The safety, accessibility, pleasantness, and aesthetics of the street environment were correlated with increased walking and perceived health status [32,34,41,49]. Of these, the safety and accessibility of the street environment were the prominent attributes affecting the mobility of vulnerable groups (e.g., older adults and children).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations